Postcolonial Anti-Racism and Its Other (KULT_online, 2010)
Referring to postcolonial and cultural studies, Iman Attia introduces the concept of “anti-Muslim racism” in order to criticise resentments against Islam. While this approach is promising, her way of applying it is reductionist, overly generalising, and methodologically questionable. Thus, as a whole, her book Die "westliche Kultur" und ihr Anderes (“Western Culture” and its Other) is more of a contribution to political polemics than to scholarship.